Role of MRI in evaluation of seizure disorder in Southern Rajasthan, India - Chabarwal, Swati; Kardam, Narendra Kumar (International Journal of Research in Medical Sciences, 2019)
Background: The objectives are to identify and study structural abnormalities in the brain that associated with seizures, spectrum of findings in patients with seizures, classify seizure type and syndrome and to evaluate role of MRI in postoperative seizures. Methods: A total of 110 patients, those referred from various outdoor/indoor departments with the history of seizure were included after fulfilling the inclusion criteria. Detailed history, appropriate clinical examinations and biochemical investigations were recorded. All MRI scans were performed on a 1.5 T Philips Achieva. Sequences were used according to MR Imaging protocol of seizures. Observation was made and analysed using descriptive tools and scientific methods. Results: Among 110 patients’ majority (41%) were normal, 20% had cerebral infarct with gliosis followed by NCC 7.2%, atrophy 5.45%, tuberculosis 11%, venous thrombosis 3.64%, developmental malformations 3.64%, glioma 1.82%, cavernoma 1.82%, tuberous sclerosis 1.82%, meningioma 0.91%, cerebral abscess 0.91% and Sturge-weber syndrome 0.91%. Most of the patients with cerebrovascular causes and male predominance 61.8%. Conclusions: The present study was a prospective study. Spectrum of MRI findings related to vascular, developmental, infection and neoplasm was identified. MRI is noninvasive modality with no radiation hazard, excellent gray white matter resolution and multiplanar imaging capability. MRI helps in detection of subtle lesions responsible for seizures. Present study observed that MRI with appropriate imaging protocols add sensitivity and specificity in evaluation of seizures.